Building Religious Pluralism of Multicultural Society in Indonesia - Basyir, Kunawi; Ag., M. (International Journal of Engineering and Technology, 2019)
Indonesia is a country that rich of diversity and difference either ethnics, cultures, tribes or religions. With these diversity and difference, it then becomes a factor of integration and unity so that leads Indonesia to the independence of the state. However, along with the development of modernization, Indonesia experiences with a new phase particularly in 1998s when comes to the fall of new regime government and where the political desire is mainly contested along the freedom of tought and willed so that impact on the uncondusive social order. Since that periods and till today religious experience of multicultural society of Indonesia alaways comes with conflict and violance. It then has inflicted restlessness and in-depth concern in the country which is full of pluralist endowment. Therefore, for the last decade Indonesia is not only renowned as the state with â€œBhineka Tunggal Ekaâ€ but also the numerous challenges and problems resulted from ethnic, religion, socio-cultural diversity (plural). Existence of pluralism and multiculturalism in Indonesia will be in danger. Such condition constitutes the effect of modernization and globalization for bringing such changes in thinking by religious people who tend to be agresive and exclusive. The condition needs serious concern by all elements starting from government, religious figure, people figure and all social communities in general as a blockhouse of multiculturalism and pluralism. As an approach used by Muslim and Hindu people in Bali when there is an unfortunate outbreak of Bom Legian (Legian Bombing), they involves all elements so that humanity, just, equality problem are quickly accomplished and Bali can raise again to become a glowing and beautiful Bali and can be used as one of the references to build religious pluralism in Indonesia. Â Â